2006
DOI: 10.1111/j.1600-6143.2006.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transplantation of Kidneys from a Donor with Myoglobinuric Acute Renal Failure

Abstract: The shortage of donor organs is reflected in the growing number of patients on the waiting list for kidney transplantation worldwide. It seems to be sensible to expand the scarce donor pool by the cautious use of extended donor criteria. Kidneys from a 21-year-old deceased donor road traffic accident victim who suffered acute renal failure (ARF) due to myolysis were transplanted. Both transplantations were successful after an initial period of delayed graft function. Therefore, kidneys from deceased donors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
2
9
0
2
Order By: Relevance
“…Rhabdomyolysis and acute renal failure (ARF) may be considered a contraindication for kidney donation, especially when the donor is anuric . There are a few case reports in the literature of kidney transplantation from donors with rhabdomyolysis, but the long‐term renal function of these grafts is unknown . Here, we report our initial experience of kidney transplantation from donors with severe rhabdomyolysis and ARF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhabdomyolysis and acute renal failure (ARF) may be considered a contraindication for kidney donation, especially when the donor is anuric . There are a few case reports in the literature of kidney transplantation from donors with rhabdomyolysis, but the long‐term renal function of these grafts is unknown . Here, we report our initial experience of kidney transplantation from donors with severe rhabdomyolysis and ARF.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 There are a few case reports in the literature of kidney transplantation from donors with rhabdomyolysis, but the long-term renal function of these grafts is unknown. [9][10][11][12][13] Here, we report our initial experience of kidney transplantation from donors with severe rhabdomyolysis and ARF.…”
Section: Introductionmentioning
confidence: 99%
“…Despite ischemic damages to the renal tubule, patients with rhabdomyolysis that do not expire usually recover renal function in 10 to 14 days (3). Kidney transplants from adult donors with rhabdomyolysis have been reported to recover acceptable function (3,4). In these reports, donor CPK levels ranged from 6099 to 52,048 U/L (3,4).…”
mentioning
confidence: 99%
“…Kidney transplants from adult donors with rhabdomyolysis have been reported to recover acceptable function (3,4). In these reports, donor CPK levels ranged from 6099 to 52,048 U/L (3,4). Although delayed graft function occurred in approximately 42% of reported cases, all kidneys ultimately functioned in the short-term.…”
mentioning
confidence: 99%
“…Among the strategies employed to address the scarcity of organs for transplant is the use of kidneys from non‐standard donors. These include older donors, those with a history of diabetes, hypertension or vascular disease, and those with elevated serum creatinine (S.Cr) (1, 3). Previous studies have reported that an elevated donor S.Cr is only important in predicting the short‐term graft survival (87% survival at one yr) (4).…”
mentioning
confidence: 99%